Investigation of the antimicrobial activity of some plant extracts - Yekeler, Hümeyra Betül; Rayaman, Erkan; Çam, Muhammet Emin (Kızılay Culture and Art, 2025)
The use of antimicrobial plants in mineral water prevents the growth of pathogenic microorganisms, extends the shelf life of the product, and pro vides a natural alternative to chemical preservatives (1). Furthermore, they contribute to the addition of health-beneficial components to the beverage. In this study, the antimicrobial effects of Rubus fruticosus L. (blackberry), Olea europaea L. (olive leaf ), Punica granatum L. (pomegranate peel), Althaea offici nalis L. (marshmallow flower), Vaccinium myrtillus L. (blueberry), Ocimum ba silicum L. (basil) plant extracts were investigated. Antimicrobial activity was primarily determined by the disc diffusion method. Also, minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of plant extracts were determined. Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Staphylococcus aureus ATCC 43300, Staphylococcus epidermidis ATCC 11228, Enterococcus faecalis ATCC 29212, Pseudomonas aeruginosa ATCC 27853, and Candida albicans ATCC 90028 were used in antimicrobial activi ty tests. According to the data obtained from the disc diffusion test, Punica granatum and Vaccinium myrtillus extracts were found to generate the largest zone of inhibition on microorganisms. However, none of the plant extracts exhibited an inhibition zone for C. albicans. Considering the MIC and MBC of all plant extracts against the tested bacterial and fungal strains, the lowest MIC values were observed in Punica granatum extract (mean 3.67 mg/mL). This value was followed by Rubus fruticosus and Vaccinium myrtillus extracts with an average value of 5.17 and 5.78 mg/mL, respectively. According to these results, three of the six different plant extracts showed antimicrobial activity within the desired level. This study suggests that plant extracts may offer an innovative solution to provide antimicrobial protection in mineral water. The findings of the study encourage the use of natural antimicrobial agents as an alternative to chemical preservatives in the food and beverage industry to contribute to the development of healthier and safer products in mineral water production.
Keywords: Antimicrobial effect; Mineral water; Plant extracts; Natural preservatives